Diversificação da dívida: uma análise em empresas brasileiras listadas na BM&FBOVESPA - Dalcin, Lúcio (2018)
The following work aims to analyze the structure of the debts of Brazilian companies registered at BM&FBOVESPA. More specifically, to define the types of debts related to their indexers, calculate the degree of diversification of such debts of companies and identify the variables that impact from them. The method used on the research is based in regression models with panel data with fixed effects. The categorization of the debt types was made through their indexer, because it is believed that it is the proper method to evaluate debts and differentiate them. Therefore, the following types of debts were analyzed: Brazilian Development Bank, Lease Operations, Interbank Deposit Rate, Long-term interest rate, Debentures, Foreign Currency, Special System for Settlement and Custody, Equipment and machinery financing, Referential Rate, General prices index – Internal Availability, Market general price index, Extended consumer price index and other types of debts. After the types of debt were identified, a measure capable of distinguishing different companies, with or without registered debts, was stablished. In order to accomplish this test, the Herfindahl- Hirschman calculation was applied, following the same method adopted by Colla, Ippolito and Li (2012) and Póvoa (2013). Finally, the dependent variable of the study was the debt diversification and the independent variables are: profitability, tangibility, total debt, Market value, market to book (M/B), size, volatility, paid dividends, assets maturities, cash in hand, market leverage, research and development expenses (P&D), distance from financial difficulties and crisis. As the main results, the study has found that only 25 companies have IHH equals 1, on the other hand, although HHI values near zero were found, no HHI value is equals zero, showing that there are no companies which are totally diversified in the sample used in the research. It was also verified that the companies which have the biggest debts are the ones that have more different types of debts on their capital structure, and the indexers BNDES, SELIC, IGPDI and IGPM impact this structure, so that the more debts in these indexers, the more diversified in debts is the company. On the other hand, the indexers Foreign Currency and Referential Rate cause diversification decrease, in other words, the more debts in these indexers, the smaller debt diversification. Another important information found of this study was that the indexer Foreign Currency was the main indexer used by the companies.